Optimalisasi pendataan sertifikat wakaf upaya kecematan ujung pandang dalam menjaga legalitas dan keberkahan tanah wakaf - Fitri Sri Ramadhani M; Suriyati; Alda Risma; Muh. Fakhri Rawatib; M. Husni Mubarak (Jurnal Humaniora & Sosial Sains, 2025)
Waqf is an act of worship with social and economic dimensions that plays a vital role in supporting the welfare of the community. In Indonesia, the concept of waqf has been known since the 13th century and is generally understood based on the Shafi'i school of thought, which emphasizes the eternal nature of waqf. However, administrative issues, particularly regarding the legality of waqf land, remain a challenge, including in Ujung Pandang District. This study aims to examine the data collection and certification process for waqf land carried out by the Ujung Pandang District Office of Religious Affairs (KUA), using a descriptive qualitative approach through direct observation of mosques and interviews with mosque administrators. The results show that of the nine plots of waqf land covering 0.68 hectares in the area, only one plot has been certified, while the rest lack formal legal status. The main obstacles include a lack of understanding of legal procedures, limited funding, and suboptimal assistance from the authorities. The Ujung Pandang Office of Religious Affairs (KUA) plays an active role in addressing these obstacles through systematic data collection and the preparation of reports as a basis for further policymaking. This study emphasizes the importance of optimizing data collection and certification of waqf land as an effort to maintain the blessings and sustainability of the socio-economic function of waqf, as well as the need for synergy between the KUA, the community, and related institutions to realize the legality and sustainable legal protection of waqf assets.